Continuous melt processing of Bi-2212/Ag dip coated tapes - Morgan, C; Henry, B; Eastell, C; Goringe, M; Grovenor, C (1997)
Bi-2212/Ag tapes have been produced using a continuous dip coating and partial melt processing technique. The role of the annealing and melt processing temperatures on the microstructure and current-carrying properties of the tapes are reported. In particular, the effect of a pre-anneal heat treatment on the residual carbon content from the organic binder has been investigated, in order to improve critical currents. These results have been used to optimise the temperature profile of a multiple-zone tube furnace through which continuous melt processing of the tape is possible. Multiple metre lengths of superconducting tape have been produced and wound into coils. Critical currents of 8.3A in statically processed tapes and 1.9A in continuously processed tapes have been achieved at 77K, zero field. © 1997 IEEE.